Planning and organization of nutritional care in confronting excess weight and obesity in the City of Recife (Research, Society and Development, 2021)
Objective: This study sought to investigate the prevalence of overweight and obesity in the city of Recife, to analyze the process of Planning and Organization of Nutritional Care in SUS, in combating overweight and obesity and to encourage empowerment for practices of self-care and social participation. Methodology: using an ecological method, with an analytical character and a qualitative approach from the perspective of the intersectoriality of Public Food and Nutrition Policies, using secondary data and public reports on the nutritional status of individuals monitored by Primary Care teams at Health registered at SISVAN Web, aged between 20 and 59 years. Results: It was observed that the prevalence of overweight and obesity in the municipality has been increasing between the years 2010 to 2019, in both sexes, being more frequent in the male population. Final Considerations: Knowledge of the local reality can help to better define the priorities of the government's agenda.